Reclaiming voices and disputing authority: a feminist dialogics approach in reading Kee Thuan Chye’s plays - Erda Wati Bakar,; Noraini Md Yusof,; Ravichandran Vengadasamy, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2016)
Kee Thuan Chye in all four of his selected plays has appropriated and reimagined history by giving it a flair of contemporaneity in order to draw a parallel with the current socio-political climate. He is a firm believer of freedom of expression and racial equality. His plays become his didactic tool to express his dismay and frustration towards the folly and malfunctions in the society. He believes that everybody needs to rise and eliminate their fear from speaking their minds regardless of race, status and gender. In all four of his plays, Kee has featured and centralised his female characters by empowering them with voice and agency. Kee gives fair treatment to his women by painting them as strong, liberated, determined and fearless beings. Armed with the literary tools of feminist dialogics which is derived from Bakhtin’s theory of dialogism and strategies of historical re-visioning, this study investigates and explores Kee’s representations of his female characters and the various ways that he has liberated them from being passive and silent beings as they contest the norms, values and even traditions. It is found that the dissecting voices of Kee’s female characters contain veiled messages and it is dialogic in nature. Their voices are caught in between opposition and struggle which echoes Kee’s manifested resistance towards the authority’s establishment of power.